Implementasi Pembelajaran Kitab Mabadi’ul Fiqhiyyah dalam Penguasaan Praktik Ibadah Siswa Kelas X SMK Andalusia Wonosobo - Adham Sofyan Afandy; Fatkhurrahman Fatkhurrahman; Ali Imron (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research is motivated by the importance of understanding and mastering religious practices for students, particularly in carrying out daily worship in accordance with Islamic jurisprudence. Learning the Mabadi'ul Fiqhiyah textbook is one way to provide a basic understanding of religious topics, such as purification, ablution, prayer, and ghusl after janabat. This study used a qualitative approach with a descriptive method. Data collection techniques were observation, interviews, and documentation. The subjects were teachers, program coordinators, and tenth-grade students at Andalusia Vocational High School, Wonosobo. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings show that the implementation of Mabadi'ul Fiqhiyah learning is carried out through the